Down-regulation of torp4a, encoding the Drosophila homologue of torsinA, results in increased neuronal degeneration. - Muraro, N.I.; Moffat, K.G. (Journal of Neurobiology, 2006)
Early-onset torsion dystonia is a dominant motor disorder linked to mutations in torsinA. TorsinA is weakly related to a superfamily of chaperone-like proteins. The function of the torsin group remains largely unknown. Here we use RNAi and over-expression to analyze the function of torp4a, the only Drosophila torsin. Targeted down-regulation in the eye causes progressive degeneration of the retina. Conversely, over-expression of torp4a protects from age-related degeneration. In the retinas of young animals, a correlation with the lysosome-related organelle, the pigment granule, is also observed. Lowering torp4a causes an increase in pigment granules, while over-expression causes loss of granules. We have performed a screen for genetic interactors of torp4a identifying a number mutants, including two members of the AP-3 complex. Other genetic interactors found included genes related to actin and myosin function. Our findings implicate the Drosophila torsin, torp4a, to function with molecules consistent with already predicted roles in the endoplasmic reticulum/nuclear envelope compartment, and have identified potential new interactions with AP-3 like components.